The fourteenth goldfish - Holm, Jennifer L. (Random House, 2014)
Ellie's scientist grandfather has discovered a way to reverse aging, and consequently has turned into a teenager--which makes for complicated relationships when he moves in with Ellie and her mother, his daughter.